Effect of pH and TPP concentration on chemico-physical properties, release kinetics and antifungal activity of Chitosan-TPP-Ungeremine microbeads. (1st September 2018) - Moeini, Arash; Cimmino, Alessio; Dal Poggetto, Giovanni; Di Biase, Mariaelena; Evidente, Antonio; Masi, Marco; Lavermicocca, Paola; Valerio, Francesca; Leone, Antonella; Santagata, Gabriella; Malinconico, Mario
Graphical abstract: Highlights: Chitosan_Ungeremine_TPP microbeads were obtained by external gelation method. Microbeads were stable and showed high loading efficiency at low pH. Ungeremine took actively part to crosslinking process by ionic interaction with Ch and TPP. Ungeremine was not active against Penicillium roqueforti, a bakery food contaminant. Releasing kinetics could be tailored depending on bakery food pH and TPP concentration. Abstract: In this study, chitosan based microbeads containing Ungeremine, an antimicrobial alkaloid particularly active against Penicillium roqueforti, a filamentous fungus responsible of the bakery products deterioration, were prepared by external gelation by using sodium tripolyphosphate (TPP) as crosslinking agent. The stability of the beads, as well as the loading efficiency of the bioactive molecule, were assessed at different pH and TPP concentrations resulting particularly enhanced at low pH. All the microbeads evidenced antimicrobial activity against Penicillium roqueforti . The release kinetics of Ungeremine was tailored by opportunely modulating pH and TPP concentrations. Morphological analysis evidenced the improvement of the structural crosslinking density of microbeads including Ungeremine and spectroscopic analysis emphasized the active participation of Ungeremine to the crosslinking process occurring between chitosan and TPP. Finally, thermogravimetric analysis confirmed the increasing of free volume in three-dimensional networks and their liability to thermal degradation.